2014
DOI: 10.1080/09585192.2014.919949
|View full text |Cite
|
Sign up to set email alerts
|

Idiosyncratic deals and good citizens in China: the role of traditionality for recipients and their coworkers

Abstract: The purpose of this study is to investigate the relationship between idiosyncratic deals and organizational citizen behavior (OCB). How traditional Chinese values moderate the relationship between idiosyncratic deals and OCB is examined from the perspectives of recipients and coworkers. Survey data were provided by 359 supervisor-subordinate dyads. Recipients of idiosyncratic deals are positively associated with their OCB-I, and the positive relationship between them is strongest for individuals with high perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 46 publications
1
41
0
1
Order By: Relevance
“…). Furthermore, cultural context and national norms may be expected to impact employee OCB (Huo, Luo and Tam ). For instance, cultural relationship types and traditional norms such as obligation and authority are likely to impact employee OCB in China (Farh, Earley and Lin ; Wang and Wong ).…”
Section: Theory and Hypothesis Developmentmentioning
confidence: 99%
“…). Furthermore, cultural context and national norms may be expected to impact employee OCB (Huo, Luo and Tam ). For instance, cultural relationship types and traditional norms such as obligation and authority are likely to impact employee OCB in China (Farh, Earley and Lin ; Wang and Wong ).…”
Section: Theory and Hypothesis Developmentmentioning
confidence: 99%
“…For example, when employees receive flexible idiosyncratic deals, their coworkers may take on increased workloads; likewise, if employees receive developmental idiosyncratic deals, their coworkers may miss out on career development opportunities because of limited budgets. Recipients of idiosyncratic deals, therefore, may feel the need to help their coworkers or extend extra effort in the workplace to 'keep the peace' or mitigate jealousy (Huo et al, 2014).…”
Section: Underlying Theory To Explain I-deals' Effects On I-dealers Amentioning
confidence: 99%
“…An et al (2010) confirmed that developmental i-deals are not only positively related to employees' interpersonal helping behaviors which benefits their immediate managers and coworkers (OCB-I), but also related to helping behaviors which contributes to their employing organization's welfare (OCB-O). Huo et al (2014) reached inconsistent conclusion that i-deals have a significant and positive impact on OCB-I but not on OCB-O. A reasonable explanation seems to be that workers prefer to reciprocate employers who directly negotiate i-deals for them, and they attempt to mitigate a perceived sense of injustice by coworkers by engaging in interpersonal helping behaviors (i.e.…”
Section: Positive Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…As illustrated in the summary of research on co-worker reactions in Table 1, the most common theoretical lens that has been applied to the study of co-worker reactions to i-deals has been justice theory and its variants (e.g., Greenberg et al, 2004; Lai, Rousseau, & Chang, 2009; Marescaux & De Winne, 2015), which may explain the limited number of outcomes that have been theorized thus far (e.g., fairness judgments and related outcomes such as co-worker acceptance of a colleague’s hypothetical future i-deal, co-workers’ organization citizenship behaviors [OCBs], co-worker’s basis/rule for judging distributive fairness of an i-deal; Huo, Luo, & Tam, 2014; Lai et al, 2009). This sparse research is silent regarding other outcomes and other cognitive and emotional mechanisms that likely predict employee reactions to colleagues’ i-deals, as evidenced by several recent calls by i-deals scholars for such research (Guerrero & Challiol-Jeanblanc, 2016; Ng & Lucianetti, 2016).…”
mentioning
confidence: 99%